2020
DOI: 10.1038/s41598-020-70044-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of radiological peritoneal cancer index in malignant peritoneal mesothelioma: national cohort study

Abstract: Malignant peritoneal mesothelioma (MpeM) is a rare cancer of the mesothelial cells of the peritoneum. Computed tomography (CT) is considered the standard for first-line imaging of MPeM, diagnosis and risk stratification remains challenging. Peritoneal cancer index (PCI), as assessed by CT, is utilized in the prognostic assessment of other malignant intra-abdominal conditions; however, there is limited data concerning the utility of PCI in the diagnosis and workup of MPeM. We studied a retrospective cohort of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…PCI for peritoneal spread of the disease is evaluated using either laparotomy or computed tomography. A high PCI score is associated with a worse prognosis [ 12 ]. However, the subclassification of epithelioid mesothelioma and data on the peritoneal cancer index are not available in the SEER registry.…”
Section: Discussionmentioning
confidence: 99%
“…PCI for peritoneal spread of the disease is evaluated using either laparotomy or computed tomography. A high PCI score is associated with a worse prognosis [ 12 ]. However, the subclassification of epithelioid mesothelioma and data on the peritoneal cancer index are not available in the SEER registry.…”
Section: Discussionmentioning
confidence: 99%
“…PCI score (range 0-39) can evaluate the spread of peritoneal cancer during laparotomy or CT examination. 24 The residual tumors were intraoperatively classified by CC scores, including 4 groups: CC-0 (no residual tumors), CC-1 (residual tumor with a diameter of <2.5 mm), CC-2 (residual tumor with a diameter of between 2.5 mm and 2.5 cm), and CC-3 (residual tumor with a diameter of >2.5 cm). 25 Previous study had shown that PCI score and CC score were related to the prognosis of PeM.…”
Section: Discussionmentioning
confidence: 99%
“…A radiological study of 59 patients with peritoneal mesothelioma showed significantly higher rPCI (34 vs. 17), large volume upper abdominal disease, small bowel and mesenteric disease among patients who had incomplete cytoreduction for malignant peritoneal mesothelioma compared to those who had complete cytoreduction [21]. CT or MRI-derived rPCI of ≥ 30 was associated with worse survival and rPCI of ≤ 19 was associated with improved survival in another study of 53 patients with malignant peritoneal mesothelioma [49]. Thus, CT is a good technique for identifying patients with high PCI disease, who may not benefit from CRS and HIPEC.…”
Section: P-peritoneal Cancer Index (Pci)mentioning
confidence: 98%